Diversity of Arthropods in Sweet Corn - Sangkhae Nawanich; Wiboon Chongrattanameteekul; Pojjanee Supamongkol (Agriculture and Natural Resources, 2010)
An experiment on the diversity of arthropods was carried out at the National Corn and Sorghum Research Center to determine the diversity and abundance of arthropods in two growing seasons of sweet corn, during June-October 2008. Sampling data was recorded by a visual count method and a sample of 210 plants was observed by a stratified random sampling technique. The type and number of arthropods were recorded at 7, 14, 24, 31, 39, 45, 53 and 63 d after emergence. Diversity of arthropods was analyzed by the Shannon-Wiener diversity index. The results revealed that in the rainy season, 43 types of arthropod were found and 32 types were found in the late-rainy season. The diversity indices ranged from 0.5956 to 2.7013, with the highest value (H′ = 2.7013) at 31 d after emergence in the rainy season. However, in the late-rainy season the diversity indices ranged from 0.2656 to 1.0908, with the highest value (H′ = 1.0908) at 14 d after emergence. In addition, insects in the Aphididae family made up the largest fraction of arthropods found in the rainy and late–rainy seasons with 4,216 and 39,199, respectively. Therefore, the rainy season had the higher diversity index and type accumulation than the late-rainy season, while the number of individuals was higher in the late-rainy season.